2020 ASEE Virtual Annual Conference Content Access Proceedings
DOI: 10.18260/1-2--35274
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Dynamics Using a Flipped Classroom Blended Approach

Abstract: in 2009. She is a Lecturer in the Mechanical and Aerospace Engineering Department at the University of Central Florida (UCF), where she teaches courses in the areas of system dynamics, controls and biomedical engineering. Her current research interests include engineering education with focus on blended learning, project based learning, digital education and design education. She received the Excellence in Undergraduate Teaching Award at UCF. Dr. Anchalee NgampornchaiAnchalee Ngampornchai is an interculturalis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
(17 reference statements)
1
4
0
Order By: Relevance
“…The results in Figure 3 corroborate the fact that the students perceive the lecture video-based blended instruction as an effective way to learn course materials. These results are consistent with data reported by similar studies conducted on lecture video-based blended learning in engineering courses [2], [21]. Student satisfaction and student attitude toward the blended course were also gauged through the survey questions.…”
Section: C Student Perception and Student Satisfactionsupporting
confidence: 88%
See 1 more Smart Citation
“…The results in Figure 3 corroborate the fact that the students perceive the lecture video-based blended instruction as an effective way to learn course materials. These results are consistent with data reported by similar studies conducted on lecture video-based blended learning in engineering courses [2], [21]. Student satisfaction and student attitude toward the blended course were also gauged through the survey questions.…”
Section: C Student Perception and Student Satisfactionsupporting
confidence: 88%
“…For example, the implementation of a blended engineering master's program in Spain not only increased enrollment, but also resulted in increased students' satisfaction, interaction with instructors, and learning performance [8]. The blended approach has been utilized in large-size engineering classes and the results have shown that students were more satisfied and that they believe they had more opportunities to apply their knowledge [2], [4]. Similarly, when the blended approach was used in a biology class, the findings showed that students learned deeper and their grades were better than those learning in the traditional classroom [9].…”
Section: Introductionmentioning
confidence: 99%
“…The lightboard gives the teachers more dynamism to express their ideas and present the course material (Sidlauskas et al, 2021). The teaching methodology is crucial in taking advantage of the lightboard's characteristics (Choe, 2017;S. Pal et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Many of the other references that discuss flipping Dynamics only involved partial flipping for a selected number of topics [5][6][7][8]. In [5] a total of six topics were flipped.…”
Section: Introductionmentioning
confidence: 99%
“…Another study, [8], discusses a hybrid course in which 50% of the material was delivered online. Assessment results presented indicate that the videos were, in general, viewed positively.…”
Section: Introductionmentioning
confidence: 99%